2011
DOI: 10.1590/s0034-737x2011000600016
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de bezerros alimentados usando de sucedâneo até 56 dias de idade

Abstract: Performance of calves fed milk replacer until 56 days of ageThirty male Holstein calves were designed to two groups, kept in pasture since they were five days, and they were fed with commercial pelleted starter concentrate, and whole milk (control group) or milk replacer made with soy protein, wheat milk and whey (treatment group), in one hour a day, until 56 days. The calves had access ad libitum to water and mineral salt. Everyone was weighted weekly, and measured. The stature development didn't differ betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
2
0
3
Order By: Relevance
“…França et al (2011) reported similar results related to body weight, with no differences between treatments and no interaction between treatment and age. The weight loss during the first weeks of age was expected due to high incidence of diarrhea observed during this period because of animals immunity fall.…”
Section: ------------------------------------------------------------supporting
confidence: 53%
“…França et al (2011) reported similar results related to body weight, with no differences between treatments and no interaction between treatment and age. The weight loss during the first weeks of age was expected due to high incidence of diarrhea observed during this period because of animals immunity fall.…”
Section: ------------------------------------------------------------supporting
confidence: 53%
“…Mesmo com variação numérica nos valores das pesquisas, fica claro que os animais que recebem leite integral em sua dieta líquida na fase de cria têm o desempenho melhorado. Fato este também observado na literatura, cujas pesquisas relatam que o desempenho dos bezerros que recebem sucedâneo é em média de 20% a 30% inferior aos animais tratados somente com leite integral (França et al, 2011;Boito et al, 2015).…”
Section: Resultsunclassified
“…Boito et al 2015atribuíram esse efeito ao valor biológico do sucedâneo, que é menor que o do leite integral e apresenta uma menor taxa de absorção dos nutrientes quando comparados ao leite integral. Além de atributos nutricionais influenciarem no ganho de peso dos animais, outro fator determinante diz respeito às características organolépticas dos substitutos lácteos, o que dificulta a adaptação dos animais a essa dieta (França et al, 2011;Schäff et al, 2018).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The high inclusion observed is a consequence of the non-milk protein source included in MR. Soybean and wheat are the most used ingredients as non-milk protein source in MR, and besides the premise that soy proteins are less digestible than milk proteins, because of the immature digestive tract of young calves (Tanan, 2005), soy proteins may contain anti-nutritional factors, such as trypsin inhibitor, antigenic proteins (glycinin and β-conglycinin), and indigestible sugar (verbascose and oligosaccharides; Huisman and Jansman, 1989), and those issues may be associated with digestive disruptions (França et al, 2011;Morrison, 2015) and the lower small intestine development in calves (Drackley et al, 2006). Even with industrial treatments of vegetable protein sources, soy and wheat protein inclusion in MR may be linked to calves' low performance.…”
Section: Adg and Digestibilitymentioning
confidence: 99%